De werkdag : de geschiedenis van de strijd voor arbeidsduurvermindering - Maes, Jef; Van Rie, Kristien; Muelenaer, Guido (Antwerpen: EPO, 1985)
"Jef Maes, Kristien Van Rie ; onder redactie van Guido Muelenaer"